Utilizing Multimedia Technology in Digital Learning Content Development - Tuharea, Jumiati; Yanuarsyah, Iksal; Nitin, Mahon; R, Muh Rafli; Jie, Lie; Jixiong, Cai (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
The development of information and communication technology is growing rapidly. Many positive impacts are obtained, especially in the field of education. Teachers and students find it easy to do the learning process in the classroom. If they use technology in digital learning. Access to new knowledge, information from various parts of the world, learning methods that suit student needs, and others can be reached with just one tap of the finger. It is so easy to compete in this globalization era. One of them is by utilizing multimedia technology in the development of digital learning content, so that if utilized optimally, it will get great benefits. The results of content creation are more interesting and favored by the audience. The purpose of this research is to facilitate the development of digital learning content by utilizing multimedia technology as much as possible, so that learning objectives for students can be achieved properly and optimally. For example, by creating educational content about one of the learning materials on YouTube which contains direct explanation by the teacher in an interesting place. And the content is supported by features that are interesting and not boring. The method used in this research is quantitative method. Data obtained through distributing questionnaires to students. The questionnaire was created by utilizing Google form. The results of this study explain that utilizing multimedia technology properly in creating digital learning content will provide benefits for teachers and students in the learning process. The conclusion of this study is that the utilization of multimedia technology has a positive influence and provides space for teachers to provide digital learning content easily and creatively. The limitation of this study is that researchers only conducted research at the school or madrasa level which in fact requires the use of multimedia technology in learning.